1992
DOI: 10.2527/1992.70113304x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of milk production, milk expected progeny difference, and calf weaning weight in angus and simmental cow-calf pairs

Abstract: Milk EPD, used to predict the milk production potential of a parent's daughters, have been reported by all major cattle breed associations. Our objectives were to determine the relationship of milk EPD of a dam to actual milk production (both fluid and components) and offspring weaning weight. Angus (AN; n = 114) and Simmental (SM; n = 82) cows were machine-milked at approximately 60, 104, and 196 d postpartum after overnight calf removal. In addition, one herd of AN was also milked at approximately 35 and 145… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
2
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 73 publications
8
33
2
7
Order By: Relevance
“…Several previous studies have reported milk fat contents for beef cattle. For instance, Melton et al (1967) reported a value of 2.87% fat in Charolais cows and 2.79% fat for other beef breeds (Angus and Hereford) assessed under the same management practices, and similar results were reported by Marston et al (1992) for Angus and Simmental cows (3.7% and 3.6% fat, respectively). A recent study also reported a mean fat level of 2.92% in Creole and Guzerat cows and their F1 crosses, with no observed differences among these genetic groups (Martínez Velázquez et al, 2010).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Several previous studies have reported milk fat contents for beef cattle. For instance, Melton et al (1967) reported a value of 2.87% fat in Charolais cows and 2.79% fat for other beef breeds (Angus and Hereford) assessed under the same management practices, and similar results were reported by Marston et al (1992) for Angus and Simmental cows (3.7% and 3.6% fat, respectively). A recent study also reported a mean fat level of 2.92% in Creole and Guzerat cows and their F1 crosses, with no observed differences among these genetic groups (Martínez Velázquez et al, 2010).…”
Section: Resultssupporting
confidence: 65%
“…Consequently, the contents of milk components and their variations have been proposed as significant factors influencing the development of calves during the pre-weaning period (Brown et al, 2002;Brown and Lalman, 2010;Martínez Velázquez et al, 2010). Previous studies have examined the percentages of milk components and their relationships with pre-weaning growth (Rutledge et al, 1971;Totusek et al, 1973;Mondragon et al, 1983), and other studies have examined the same correlations of growth with milk components by weight (Jeffery and Berg, 1971;Marston et al, 1992;Martínez Velázquez et al, 2012). However, the milk composition in Charolais cattle and its relationship with pre-weaning growth have not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à relação da produção de leite e peso à desmama foi verificado aumento de 0,025 kg, para cada quilograma a mais de leite consumido pelo bezerro, apresentando Y= 151,45 + 0,025X como equação de regressão. Este resultado está dentro da amplitude de valores observados, sendo semelhante aos de raça de duplo propósito como a Simental, e de vacas Aberdeen Angus suplementadas (Marston et al, 1992), esta constatação pode ser atribuída ao bom desempenho ponderal que as vacas apresentaram durante este experimento (0,104 kg + 0,027). A correlação entre produção de leite total e peso do bezerro à desmama verificada foi de 0,33, resultado muito semelhante ao de Marston et al (1992) que trabalhando com vacas suplementadas, obtiveram correlação entre produção de leite total e peso à desmama de 0,30 na mesma raça e 0,47 para raça Simental, raça com maior potencial de produção de leite.…”
Section: Tabela I Produção Diária De Leite (Kg) (Pdl) E Ganho Médio unclassified
“…A influência da produção de leite durante o período de lactação é maior nos primeiros meses do bezerro, pela grande dependência do leite nesse período (Melton et al, 1967;Marston, 1992). No Brasil, trabalhos que avaliaram o desempenho de bezerros no período pré-desmama encontraram correlações fenotípicas entre produção de leite e peso à desmama que variaram de 0,47 a 0,93 (Moletta et al, 1989;Albuquerque et al, 1993;Alencar et al, 1996).…”
Section: Introductionunclassified
“…Thus, there have been numerous data on the modification of nutritional management to increase milk production of the cow (Marston et al 1992). On the other hand, feeding energy and/or protein supplements in the form of creep has been shown to improve preweaning weight gains of calves (Lusby 1986;ZoBell and Goonewardene 1989).…”
mentioning
confidence: 99%